Remark on the Paper by Rao And Kakehashi (2005) - Saralees Nadarajah (Mathematical Biosciences and Engineering)
The paper by Rao and Kakehashi [1]uses the Weibull distribution (given by equation (3) in the paper)and a truncated version of it (given by equations (4) and (5))to model HIV/AIDS data in India.After a careful reading, I have found that all of the results presentedin the appendix are incorrect (starting with equation (11) itself).Instead of pointing out all of the specific errors, I have chosen to give the correct formulas (and a brief outline of their derivation)for the $r$th moment of the truncated Weibull distribution.